Revitalisasi MCK Komunal Ramah Lingkungan Berbasis Participatory Action Research Sebagai Upaya Peningkatan Kesehatan Masyarakat Di Desa Salak, Sawahlunto - Oktomalioputri, Biomechy; Noverial, Noverial; Dillasamola, Dwisari; Fahri, Idris Al (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Access to proper sanitation facilities is an essential factor in improving public health. In Salak Village, Sawahlunto, more than 20% of households lack adequate bathing, washing, and toilet (MCK) facilities. The existing communal MCK was severely damaged and repurposed, resulting in its disuse by residents. This condition has led to insufficient access to basic sanitation and low implementation of clean and healthy living behavior (PHBS). This program employed a Participatory Action Research (PAR) approach, emphasizing active community participation in every stage of the activity. The stages included field observation, problem identification, joint planning, implementation of environmentally friendly communal MCK revitalization, and PHBS education. Data were collected through interviews, focus group discussions (FGDs), and pre–post activity surveys involving 50 household heads as MCK users. After the revitalization, 88% of residents used the MCK regularly. A total of 76% of respondents demonstrated increased knowledge and practice of PHBS, particularly in handwashing habits and liquid waste management. The MCK now features a closed drainage system, rainwater harvesting tank, and natural lighting, making it more environmentally friendly. This program demonstrates a participatory revitalization model that not only improves infrastructure but also strengthens community empowerment in maintaining public facility sustainability. The PAR approach distinguishes this program from similar initiatives by fostering social ownership and shared responsibility. The success of this program has contributed to improved sanitation behavior, environmental health, and social cohesion within the community.